Fulfillment of Local Content in The Era of Democratization And Digitalization In West Java - Ahsani Taqwim Aminuddin; Tryan Nugraha (Nyimak: Journal of Communication, 2026)
This study examines how networked broadcasters in West Java, Indonesia, implement a national policy mandating a minimum of 10% local content. Drawing on in-depth interviews with editorial, production, and managerial staff, combined with regulatory data, the study analyzes production and distribution practices through a political economy of communication perspective, focusing on structuration, commodification, and spatialization. The findings reveal that most "local content" is produced in Jakarta for cost efficiency and centralized control, while local bureaus contribute only a small portion of broadcast material. Media organizations adopt different structuring patterns: community-oriented autonomy (as in Radio Elshinta), a central-local hybrid format (as in MNCs), and top-down coordination (as in CNN West Java). These practices demonstrate how ownership concentration, resource inequality, and regulatory formalism shape local broadcasting, turning compliance into a symbolic, rather than a substantive, tool of democracy. Theoretically, this study extends political economy analysis by applying it to the dynamics of subnational broadcasting, demonstrating how structure and agency interact in peripheral media spaces.  Globally, these findings highlight how centralized media systems in developing democracies struggle to balance regulatory objectives with commercial imperatives—an issue relevant to debates on media pluralism, decentralization, and cultural representation beyond Indonesia. This research provides empirical and conceptual insights into how local media policies operate within broader political-economic structures.Keywords: Indonesian Broadcasting Commission, local content, network media ABSTRAKStudi ini mengkaji bagaimana lembaga penyiaran berjaringan di Jawa Barat, Indonesia, menerapkan kebijakan nasional yang mewajibkan minimal 10% konten lokal. Berdasarkan wawancara mendalam dengan staf redaksi, produksi, dan manajerial, yang dipadukan dengan data regulasi, penelitian ini menganalisis praktik produksi dan distribusi melalui perspektif ekonomi politik komunikasi, dengan fokus pada strukturasi, komodifikasi, dan spasialisasi. Temuan penelitian mengungkapkan bahwa sebagian besar "konten lokal" ternyata diproduksi di Jakarta dengan alasan efisiensi biaya dan kendali terpusat, sementara biro lokal hanya menyumbang sedikit sekali materi siaran. Organisasi media mengadopsi pola strukturasi yang berbeda: otonomi berorientasi komunitas (seperti di Radio Elshinta), format hibrida pusat-lokal ( seperti di MNC), dan koordinasi atas-bawah (seperti di CNN Jawa Barat). Praktik-praktik ini menunjukkan bagaimana konsentrasi kepemilikan, ketimpangan sumber daya, dan formalisme regulasi membentuk penyiaran lokal, mengubah kepatuhan menjadi alat demokrasi yang simbolis, alih-alih substantif. Secara teoretis, studi ini memperluas analisis ekonomi politik dengan menerapkannya pada dinamika penyiaran subnasional, menunjukkan bagaimana struktur dan agensi berinteraksi dalam ruang media periferal.  Secara global, temuan ini menyoroti bagaimana sistem media terpusat di negara-negara demokrasi berkembang kesulitan menyeimbangkan tujuan regulasi dengan tuntutan komersial—sebuah isu yang relevan dengan perdebatan tentang pluralisme media, desentralisasi, dan representasi budaya di luar Indonesia. Penelitian ini memberikan wawasan empiris dan konseptual tentang bagaimana kebijakan media lokal beroperasi dalam struktur politik-ekonomi yang lebih luas.Kata Kunci: Komisi Penyiaran Indonesia, konten lokal, media jaringan